Biotechnology of Biofertilizers - Kannaiyan, S ; Ed (Narosa publishing, 2002)
Aims to cover the basic issues in Biological Nitrogen Fixation (BNF), such as physiology, biochemistry and molecular genetics of nitrogen fixation, role of signal molecules and host gene expression in nodulation and nitrogen fixation for an understanding of these processes in symbiotic nitrogen fixing systems.